Legacy of regret [large type] - James, Jo (Linford romance library, 2008)
When Liz Shepherd unexpectedly inherits an elderly man's considerable estate, she is persuaded it is in gratitude for her kindness to him. But doubts set in when Steve Lewis, in the guise of a reporter, challenges her good luck. Was there another reason for her legacy? And why is Steve so interested? She comes to regret her inheritance and all its uncertainties -- until Steve helps her find the truth and they discover the secret of their past.